Desain Prototipe Generator Linier Magnet Permanen Rpm Rendah - Prasetyo, Septian Heri; , Hasyim Asy'ari, ST.MT (2016)
Indonesia is a maritime country that has a vast sea area. Indonesia sea conditions that has high waves can be one source of renewable energy by utilizing the ocean waves. The movement of ocean waves can be used as a driver of a linear generator for electric energy sources in coastal areas of Indonesia with the huge size and high frequency of ocean waves. This is certainly will be one of the new ways to overcome the lack of fulfillment of the electricity demand in Indonesia. This study is going to discuss the design of a prototype linear generator and analyze the effect of windings to output of the linear generator. This linear generator using a rotor with 5 pairs of ferrite permanent magnet type and 6 slot with the stator frame with amount of 200, 300, 400 and 500 windings. Linear generator able to produce the voltage at ranges as the lowest with 2.1 v in 200 windings and 100 rpm conditions and 8,1 v as the highest voltage at 500 windings and 300 rpm conditions. This generator is able to generate power up to 135.7 mW at 500 windings and 300 rpm. The data obtained from these experiments with lab scale could developed to a larger scale by varying the type of magnet used, number of windings, and speed used to generate larger power.